Landfill leachate treatment by an experimental subsurface flow constructed wetland in tropical climate countries. - Ujang, Zaini; Soedjono, E.; Salim, M. R.; Shutes, R. B. (IWA Publishing, 2005)
Municipal leachate was treated in an experimental unit of constructed wetlands of subsurface flow type. The parameters studied were organics (BOD and COD), solids and heavy metals (Zn, Ni, Cu, Cr and Pb). Using two types of emergent plants of Scirpus globulosus and Eriocaulon sexangulare, more than 80% removal was achieved for all the parameters. E. sexangulare removed organics and heavy metals better than Scirpus globulosus. A higher concentration of heavy metals in the influent did not change the removal efficiency.